Management of congenital diaphragmatic hernia with transposition of the great arteries. Issue 6 (13th April 2016) - Nagata, Hazumu; Yamamura, Kenichiro; Nagata, Kouji; Uike, Kiyoshi; Morihana, Eiji; Ihara, Kenji; Yumoto, Yasuo; Fusazaki, Naoki; Kado, Hideaki; Kato, Kiyoko; Taguchi, Tomoaki; Hara, Toshiro
Abstract: Congenital diaphragmatic hernia (CDH) is a relatively rare malformation, but it has a high mortality rate. Its association with congenital heart disease lowers survival rate due to severe acidosis and desaturation caused by persistent pulmonary hypertension of the neonate. We describe herein a case of CDH with transposition of the great arteries and intact ventricular septum, in a patient who was prenatally diagnosed, managed with extracorporeal oxygenation (ECMO) support and successfully treated with both CDH repair and Jatene procedure, with no respiratory or circulatory sequelae. In conclusion, precise prenatal estimation is essential, and ECMO is a useful therapeutic option in these complex cases.